КOГНІТИВНА МЕТАФОРА ЯК ОДИН ІЗ ЗАСОБІВ ТВОРЕННЯ ВТОРИННИХ НОМІНАЦІЙ МЕДИЧНОГО ДИСКУРСУ / COGNITIVE METAPHOR AS A MEANS OF CREATING SECONDARY MEDICAL DISCOURSE NOMINATIONS - Лариса ШУТАК; Галина НАВЧУК (Актуальні питання суспільних наук та історії медицини, 2016)
Shutak L., Navchuk G. Cognitive Metaphor as a Means of Creating Secondary Nominations Medical Discourse. Lexical organization of any language is characterized not only by correlation of existing language lexicalsemantic units, but also by the opportunity to rethink their naming that is necessary for the speaker at that moment. Therefore secondary titles often appear in speech, ie the formation of the second, even the third name for objects of extra-linguistic reality are identified by means of language. These tokens are often perpetrated by means of metaphor. The article attempts to identify the reasons and means of creating secondary names used in communicative situations specialist – specialist, specialist – non-specialist of modern Ukrainian medical discourse using metaphorical translations. Secondary titles from professional speech of medical industry workers in different communicative situations serve as a material for analysis. The article outlines the type of secondary nominations which result in metaphorical transfers. Due to the role of metaphor in the creation of a secondary nomination medical discourse. It demarks substantial (one-component), adjectival and verbal (one-component or two-component) secondary metaphorical nomination. The author determines secondary substantive metaphorical name instruments and defines reasons for their formation in typical and atypical communicative situations. The article also establishes features of metaphor adjectives and verbs as components phrases, the terms of their use and implementation of strategies of such metaphors. It is found that secondary names that are based on verb (predicate) metaphors are the most used in the medical discourse. The various reasons that cause the formation of secondary names, among which singles out the need to simplify the process of professional communication, to avoid complex medical terminology, to save time and to convey the necessary information are overviewed. Key words: secondary nomination, secondary names, methods of nomination, metaphor, medical discourse. Шутак Л., Навчук Г. Когнитивная метафора как одно из средств создания вторичных номинаций медицинского дискурса. В статье очерчен круг вторичных номинаций, которые являются следствием метафорических переносов. Обусловлена роль метафоры в процессе создания вторичных номинаций медицинского дискурса. Разграничены субстантивные (однокомпонентные), адъективные и глагольные (однокомпонентные или двухкомпонентные) вторичные метафорические номинации. Охарактеризованы вторичные субстантивные метафорические наименования инструментов, определены причины их образования в типичных и нетипичных коммуникативных ситуациях. Установлены особенности метафоризации прилагатель- ных и глаголов в качестве компонентов словосочетаний, выяснены условия их применения, а также стратегии реализации таких метафор. Выявлено, что наиболее употребляемыми в медицинском дискурсе являются вторичные названия, созданные на основе глагольных (предикатных) метафор. Обобщены причины, обусловливающие формирование вторичных наименований, среди которых выделены потребность упростить сам процесс профессионального общения, избежать использование сложной медицинской терминологии, сэкономить время, быстро и доступно передать нужную информацию и т. п. Ключевые слова: вторичная номинация, вторичные наименования, способы номинации, метафоризация, медицинский дискурс.